Drying without senescence in resurrection plants - Griffiths, Cara A.; Gaff, Donald F.; Neale, Alan D. (Frontiers in Plant Science, 2014)
Research into extreme drought tolerance in resurrection plants using species such as Craterostigma plantagineum, Craterostigma wilmsii, Xerophyta humilis, Tortula ruralis and Sporobolus stapfianus has provided some insight into the desiccation tolerance mechanisms utilized by these plants to allow them to persist under extremely adverse environmental conditions. Some of the mechanisms used to ensure cellular preservation during severe dehydration appear to be peculiar to resurrection plants. Apart from the ability to preserve vital cellular components during drying and rehydration, such mechanisms include the ability to down-regulate growth-related metabolism rapidly in response to changes in water availability, and the ability to inhibit dehydration-induced senescence programs enabling reconstitution of photosynthetic capacity quickly following a rainfall event. Currently, very little is known about the molecular mechanisms that resurrection plants employ to avoid undergoing drought-related senescence during the desiccation process. To survive desiccation, dehydration in the perennial resurrection grass S. stapfianus must proceed slowly over a period of 7 days or more. Leaves detached from the plant before 60% relative water content (RWC) is attained are desiccation-sensitive indicating that desiccation tolerance is conferred in vegetative tissue of S. stapfianus when the leaf RWC has declined to 60%. Whilst some older leaves remaining attached to the plant during dehydration will senesce, suggesting dehydration-induced senescence may be influenced by leaf age or the rate of dehydration in individual leaves, the majority of leaves do not senesce. Rather these leaves dehydrate to air-dryness and revive fully following rehydration. Hence it seems likely that there are genes expressed in younger leaf tissues of resurrection plants that enable suppression of drought-related senescence pathways. As very few studies have directly addressed this phenomenon, this review